English influence on Icelandic. The frequency and morphological properties of loanwords of English origin in Icelandic news reports - Herdís Hreiðarsdóttir 1972- (2010)
Many people feel that the English language has acquired the status of a global power. Iceland has not been excluded from the influence of English and English now serves as a ‘lingua franca’ in many domains of society. This essay attempts to explore this linguistic influence on the lexicon of modern Icelandic. In order to form an idea of the extent of this impact, an analysis was performed on news reports from Icelandic newspapers and Internet news sites. The frequency of English loanwords was documented and different morphological properties of the loanwords examined. The data consists of 60 news reports published in June 2010, randomly selected. For comparison, a random sample of 30 news texts was collected from June 1980. The survey covers loanwords of four different types: direct loans, semantic loans, loan translations and hybrids. The frequency of loanwords was analysed between different news media and different news genres: ‘domestic’, ‘foreign’ and the ‘people’. The results of the survey reveal that the frequency of loanwords is relatively low in Icelandic news reports. Loanwords of English origin account for only 1.5% of the running words in the texts from 2010 and 0.69% of the running words in the texts from 1980. However, the frequency is considerably higher in the Internet texts than the newspapers texts. The highest frequency of loanwords, 2.49%, was found in the ’people’ news genre from the Internet texts. Conversely, the lowest frequency of loanwords was found in the ‘foreign’ genre, from the 1980 sample: 0.19%. The hybrids account for approximately half of the lemmas of loanwords in both samples. Surprisingly, the direct loans are proportionally fewer in the 2010 sample: 28.57% compared to 40% in the 1980 sample.